And they lived happily ever after - Beharrie, Therese (Zebra Books/Kensington Publishing Corp., 2021)
"Successful romance author Gaia Anders has a secret: anything she dreams at night is magically written into her bestselling novels. After a lonely childhood in foster care, her dream life is the only one she trusts. Gaia's waking life just can't compare--until she gets caught in one utterly surprising, crazy-passionate, real-life kiss ... Workaholic businessman Jacob Scott has had a crush on his brother's best friend, Gaia, since forever--but he never expected to literally share her dreams. Living out their magical nighttime fantasies is explosive, but it's their waking desire turning his single-minded ways upside down. It's making him want a future he didn't think was possible ... But Gaia has secrets from her past she won't reveal. And Jacob's attempts to keep the peace in his own fractured family puts him up against her deepest fears. Soon, they're facing hard truths about who they are and what they're running from. And the only way to break this curse is realizing true love's real-life power ..."--Page 4 of cover